Vendor Management Model to Achieve Just In Time (JIT) in Material Procurement - Dwi Nurma Heitasari; Ibnu Lukman Pratama; Fanya Aulia Revalina (Journal of Applied Sciences, Management and Engineering Technology, 2025)
This research focuses on optimizing material procurement in EPC (Engineering, Procurement, and Construction) Companies by using Always Better Control (ABC) and Analytical Hierarchy Process (AHP) methods to reduce lead time to achieve Just In Time goals. The main problem faced is the long lead time of material procurement, which harms productivity, operational costs, and customer satisfaction. The ABC method was used to classify materials based on their economic value, dividing them into three categories: A, B, and C. The analysis showed that seven category A items (such as Steel Grid and Power Cable) accounted for about 62.62% of the total project cost, requiring strict inventory control. Meanwhile, the AHP method was used to determine vendor selection criteria by considering four approaches: Single Item Single Vendor (SISV), Single Item Multi Vendor (SIMV), Multi Item Single Vendor (MISV), and Multi Item Multi Vendor (MIMV). Weighting criteria through a questionnaire with 13 respondents resulted in MISV as the highest criterion (43.70%), followed by MIMV (34.30%). The validity test using consistency ratio (CR) resulted in a value of 0.06, indicating the consistency and reliability of the data. The study concluded that combining ABC and AHP methods can help EPC Companies optimize the material procurement process, reduce lead time, and improve operational efficiency. Choosing the proper vendor management model and focusing on critical items can help mitigate the risk of delays and support the smooth production process